2023
DOI: 10.1088/1361-6382/ace230
|View full text |Cite
|
Sign up to set email alerts
|

E-TEST: a compact low-frequency isolator for a large cryogenic mirror

Abstract: To achieve the expected level of sensitivity of third-generation
gravitational-wave observatories, more accurate and sensitive instruments than those of the second generation must be used to reduce all sources of noise.
Amongst them, one of the most relevant is seismic noise, which will require the
development of a better isolation system, especially at low frequencies (below 10
Hz), the operation of large cryogenic silicon mirrors, and the improvement of
optical wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The E-TEST demonstrator aims to prove the improvement in the stability of the GW mirror used in the ET interferometer under cryogenic temperature. [13][14][15][16] During the cooling down phase, the mirror may be affected by surface topology changes due to mechanical stress and induced vibrations. Kaneda et al showed the topology change of a large mirror working at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The E-TEST demonstrator aims to prove the improvement in the stability of the GW mirror used in the ET interferometer under cryogenic temperature. [13][14][15][16] During the cooling down phase, the mirror may be affected by surface topology changes due to mechanical stress and induced vibrations. Kaneda et al showed the topology change of a large mirror working at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic CMOS circuits have become increasingly popular in recent years due to their application in quantum computing [1]. Still, they also find use in a much broader spectrum of applications such as gravitational wave detectors [2]- [4], infrared focal plane arrays, positron emission tomography, and quantum technology in general [5]. Modern thin-oxide devices are usually free of the anomalies that plague thickoxide devices [6], [7], [9] and can therefore take full advantage of the benefits offered by the cryogenic environment, such as increased transconductance [9] and reduced leakage [15].…”
Section: Introductionmentioning
confidence: 99%